The Death Spiral of T Pyxidis - Joseph Patterson; Arto Oksanen; Berto Monard; Robert Rea; Franz-Josef Hambsch; Jennie McCormick; Peter Nelson; Jonathan Kemp; William Allen; Thomas Krajci; Simon Lowther; Shawn Dvorak; et al. (Middlebury, 2022)
We report a long campaign to track the 1.8 hr photometric wave in the recurrent nova T Pyxidis, using the global telescope network of the Center for Backyard Astrophysics. During 1996-2011, that wave was highly stable in amplitude and waveform, resembling the orbital wave commonly seen in supersoft binaries. The period, however, was found to increase on a timescale P/P-dot=3x10^5 yr. This suggests a mass transfer rate of ~10^-7 M_sol/yr in quiescence. The orbital signal became vanishingly weak (<0.003 mag) near maximum light of the 2011 eruption. After it returned to visibility near V=11, the orbital period had increased by 0.0054(6) %. This is a measure of the mass ejected in the nova outburst. For a plausible choice of binary parameters, that mass is at least 3x10^-5 M_sol, and probably more. This represents >300 yr of accretion at the pre-outburst rate, but the time between outbursts was only 45 yr. Thus the erupting white dwarf seems to have ejected at least 6x more mass than it accreted. If this eruption is typical, the white dwarf must be eroding, rather than growing, in mass -- dashing the star's hopes of ever becoming famous via a supernova explosion. Instead, it seems likely that the binary dynamics are basically a suicide pact between the eroding white dwarf and the low-mass secondary, excited and rapidly whittled down, probably by the white dwarf's EUV radiation.
Keywords: Astronomical sciences; Stellar astronomy and planetary systems